Analytical determination of heat flow shape factors for composite, prismatic bars of doubly-connected cross section. - Laura, P. A. A.; Sánchez Sarmiento, G. (North Holland Publishing Co., 1978)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina